PELAKSANAAN SUPERVISI KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM SMPN 03 BANJAR AGUNG TAHUN PELAJARAN 2023/2024 - Desra Afriza; Suci Hartati (UNISAN JURNAL, 2024)
This research aims to reveal the implementation of supervision by madrasa heads in improving the performance of Islamic religious education teachers at SMPN 03 Banjar Agung. The research method used is qualitative with a case study approach. Data was collected through interviews, observation and document analysis. The research results show that the implementation of supervision by madrasah heads is carried out regularly and systematically, involving observation, evaluation and feedback to teachers. The supervision carried out is inclusive and constructive, by providing motivation and encouragement to teachers. Factors that influence supervision effectiveness include understanding the concept of supervision, leadership skills, institutional support, good communication, and teacher professional development. The impact of supervision can be seen in increasing the motivation and professionalism of Islamic religious education teachers. Strategies to increase the effectiveness of supervision include strengthening understanding of supervision concepts, increasing leadership skills, increasing institutional support, improving communication and interpersonal relationships, and continuing professional development. By implementing these strategies, it is hoped that the effectiveness of madrasa head supervision in improving the performance of Islamic religious education teachers can increase, as well as make a greater contribution to the development of Islamic religious education in Indonesia.